OP0124 Treatment with cyclophosphamide for systemic sclerosis-related interstitial lung disease does not improve survival after 12 years of follow up. (15th June 2017) - Volkmann, ER; Sim, M; Tashkin, DP; Khanna, D; Clements, PJ; Roth, M; Furst, D; Pickney, A; Goldmuntz, E; Keyes-Elstein, L; Elashoff, R; Sullivan, K; et al.
Abstract : Background: Treatment with cyclophosphamide (CYC) is associated with short-term improvements in lung function, dyspnea, and radiographic fibrosis in patients with systemic sclerosis-related interstitial lung disease (SSc-ILD). 1 However, the effects of CYC therapy on long-term morbidity and mortality outcomes are unknown. Objectives: To determine whether 1 year of treatment with CYC for SSc-ILD affects long-term morbidity and mortality in patients who participated in the Scleroderma Lung Study (SLS) I. 1 Methods: SLS I randomized 158 SSc-ILD patients from 13 US SSc centers to 1 year of oral CYC versus placebo. The primary endpoint was the change in FVC%>predicted over 1 year. Twelve years after the study commenced, each study center contacted enrolled patients or designated surrogates to assess the following: mortality, cause of mortality, development of organ failure, need for transplant and functional status. We used counting process cox proportional hazard modeling to determine the variables associated with survival. The model findings were validated using a joint model of longitudinal and survival data. We also tested the model using long-term follow-up data from SLS II (CYC vs. Mycophenolate). Results: Nearly half of all SLS I patients (43%) died during the follow-up period, and only 24% remained alive in the absence of organ failure. The median follow up period for all patients was 8 years. Where known, the cause of death was attributable most often to SSc. Among patients who developed malignancy (N=13), a similar proportion were treated with CYC compared with placebo. The most common type of organ failure was respiratory failure (N=31 of 33 organ failures) defined as the need for supplemental oxygen therapy (N=29) and/or lung transplantation (N=3). There was no difference in the time to death (Figure 1 ), or time to organ failure, or time to malignancy in patients randomized to CYC versus placebo. The Cox model identified the following variables as the most important predictors of mortality: baseline skin score (HR 1.033; P =0.0038), age at randomization (HR 1.056; P <0.0001), and the course of the FVC from baseline to 24 months (HR 0.975; P =0.0215). The course of the FVC was a better predictor of mortality than the baseline FVC. The joint model identified the same variables associated with mortality. Conclusions: Treatment with 1-year of oral CYC for SSc-ILD does not decrease long-term mortality, organ failure or malignancy compared with placebo. In addition to identifying traditional mortality risk factors in SSc (i.e. increased skin score and advanced age), this study found that progression of the FVC over 2 years was a more important predictor of mortality than the baseline FVC. These findings suggest that early changes in surrogate measures of SSc-ILD progression may have important effects on long-term outcomes. References: Tashkin et al. NEJM 2006;354:2655. Disclosure of Interest: None declared